2011
DOI: 10.1063/1.3622523
|View full text |Cite
|
Sign up to set email alerts
|

A range-based method to calibrate a magnetic spectrometer measuring the energy spectrum of the backward electron beam of a plasma focus

Abstract: The electron beam emitted from the back of plasma focus devices is being studied as a radiation source for intraoperative radiation therapy applications. A plasma focus device is being developed for this purpose, and there is a need for characterizing its electron beam, particularly, insofar as the energy spectrum is concerned. The instrument used is a magnetic spectrometer. To calibrate this spectrometer, a procedure relying on the energy-range relation in Mylar® has been devised and applied. By measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…High-DR (order of 0.2–1 Gy per shot, each shot lasting 20–50 ns) experiments were performed with the PFMA-3 device (Montecuccolino Laboratory, University of Bologna). The Monte Carlo simulation of the X-ray spectrum exhibited a component at 10 keV, and a component at 50 keV with a tail of up to 200 keV [ 32 ]. The dose assessment delivered in each shot has been extensively validated using Gafchromic ® films (EBT2/3) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…High-DR (order of 0.2–1 Gy per shot, each shot lasting 20–50 ns) experiments were performed with the PFMA-3 device (Montecuccolino Laboratory, University of Bologna). The Monte Carlo simulation of the X-ray spectrum exhibited a component at 10 keV, and a component at 50 keV with a tail of up to 200 keV [ 32 ]. The dose assessment delivered in each shot has been extensively validated using Gafchromic ® films (EBT2/3) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…2,11 Measurements of the backward electron beam have been conducted by many authors, see, e.g., Refs. 12 and 13, however the results, as is to be expected, are strictly specific to every single device and extrapolation is unfeasible, hence the necessity to repeat the measurements for the device at hand, as reported in Ceccolini et al 14 As mentioned, PFMA-3 is being optimized as an x-ray generator and x-rays are obtained from the conversion of the electron beam, driven through an extraction guide to impinge on a 50 lm brass foil, therefore the need for characterising the electron beam. With this as input, MCNPX simulations were run, and they have shown that the spectrum produced is comprised of two components: one due to characteristic emission centred around 10 keV and one from bremsstrahlung centred around 30 keV and with a tail extending to 150 keV.…”
mentioning
confidence: 91%
“…The intensity of the electron beam was measured to be of the order of 10 15 electrons per discharge . Electrons are emitted during the ~50 ns of the pinch, giving a very high beam intensity, on the order of 10 22 electrons per second.…”
Section: Methodsmentioning
confidence: 99%
“…The spectrum of the electron beam was measured with a magnetic spectrometer . The measurements are described in Ceccolini et al , to which the interested reader is referred for further details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation